PENGARUH EFISIENSI KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN - Herawati, Heny (Kinerja, 2022)
This study aims to determine "The Influence of Work Efficiency and Work Motivation Performance of PT.Yuri 8 Sejahtera Bekasi”. The population in this study at PT. Yuri 8 Sejahtera Bekasi of 50 people. The analytical methods used are validity test, reliability test, descriptive statistical test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression test, simple correlation test, coefficient of determination test, F test and t test. Based on the results of the study where tcount 4.788 > ttable 1.677 and a significant value of 0.00 <0.05, it can be concluded that work efficiency has a positive and significant effect on performance and work motivation variables obtained tcount 1.984 > ttable 1.677 and a significant value of 0.014 <0.05, it can be concluded that work motivation has a positive and significant effect on performance. Based on the simple correlation test value of X1 and Y with an R value of 0.762, it can be concluded that there is a strong and positive correlation between work efficiency performance. strong and positive relationship between work motivation and sales performance. Based on the results of the coefficient of determination (R2) of 0.599, it can be concluded that work efficiency and work motivation affect performance with a value of 59.9%, while 40.1% is influenced by other variables.